Optimisasi Penjadwalan Kegiatan Guru pada SMK IDN Boarding School Jonggol dengan Penerapan Algoritma Genetika - Nuradi, Fahmi; Tundo, Tundo; Mulyana, Dadang Iskandar; Lestari, Sri (Department of Computer Engineering, Universitas Wiralodra, 2024)
This document describes guidelines for Authors in writing an article in JIMIK. This abstract section should Activity scheduling is a crucial aspect of educational management, especially in school environments with many activities and limited resources. At IDN Boarding School Vocational School, the challenges in scheduling teacher activities become increasingly complex as the number of subjects, extracurricular activities and limited resources such as space and time increase. Manual scheduling methods using spreadsheets such as Microsoft Excel take a long time and are prone to human error. This research proposes the application of a Genetic Algorithm to optimize the scheduling of teacher activities at the IDN Boarding School Vocational School. The Genetic Algorithm was chosen because of its ability to find optimal solutions through selection, crossover and mutation processes. This algorithm is able to handle various constraints in scheduling, both hard constraints (constraints that must be obeyed) and soft constraints (constraints that are desired but not mandatory). The aim of this research is to develop an automatic scheduling system that can reduce delays and the risk of errors in preparing schedules, adjust schedules quickly when sudden changes occur, and distribute teacher workload more evenly. The research results show that the application of a Genetic Algorithm can produce a more efficient and effective schedule compared to manual methods, by minimizing schedule conflicts, optimizing space use, and ensuring a more balanced distribution of teacher workload. This research not only provides a solution to scheduling problems at the IDN Boarding School Vocational School, but can also be adapted and applied to other educational institutions. Thus, this research makes a real contribution to improving the quality of educational management and teaching and learning processes in Indonesia.